PESANTREN DALAM BUDAYA PENDIDIKAN - Arief Eko Priyo Atmojo (IBDA` : Jurnal Kajian Islam dan Budaya, 2014)
Islamic education is an education which combines and accelerates world and the life after death. The aim is not only creates an intelligent man but more than that. Islamic education is intended to build a perfect man to do the task from Allah SWT to be khalifah fil ardh. Remembering the task is not an easy job, Islam provides the best education for the people. The period of Islamic education development is divided into some periods that are related to historical development and Islamic civilization. It is changed on its methods and contents. This article compares the Islamic education in prophet’s era with Islamic boarding school nowadays.